Log-polar Transformation as a Tool for Text Skew Estimation - Brodic, D.; Milivojevic, Z. N. (Elektronika ir Elektrotechnika, 2013)
The paper proposed the method for text skew detection based on log-polar transformation. The original image is transformed in the log-polar domain as well as the control ellipse. Theirs cross-correlation established the cost function. The extraction of the cost function maximums gives the text skew value in the left and right region from the centre point of transformation. The method is suitable for the printed text. It is characterized by the accuracy and computational time inexpensiveness. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.3471